2008
DOI: 10.1002/acp.1516
|View full text |Cite
|
Sign up to set email alerts
|

Imagery encoding effects on memory in the DRM paradigm: A test of competing predictions

Abstract: In three experiments the effects of imagery encoding and test format on false memory rates in the Deese-Roediger-McDermott (DRM) paradigm were examined. After generating images of individual items (Experiment 1) or integrated subsets (Experiment 2), all of which were embedded in thematically related lists, participants were surprised by a recognition memory test or one of three kinds of source tests. As predicted by a distinctive encoding hypothesis, generating individual images led to better accuracy on prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 88 publications
6
35
0
Order By: Relevance
“…This supports previous findings on imagery encoding (e.g., Foley et al, 2006Foley et al, , 2009Gunter et al, 2007), which assume imagery as a crucial factor in discrimination between studied and non-studied but strongly associated items. Moreover, imagery encoding may be treated as an active task leading to better memory (see Meijer & Van der Lubbe, 2011).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This supports previous findings on imagery encoding (e.g., Foley et al, 2006Foley et al, , 2009Gunter et al, 2007), which assume imagery as a crucial factor in discrimination between studied and non-studied but strongly associated items. Moreover, imagery encoding may be treated as an active task leading to better memory (see Meijer & Van der Lubbe, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…However, the results of the control groups showed that individual mnemonic strategies may appear, in some conditions, comparably efficient. From a theoretical perspective, the data we report converge with other recent findings demonstrating the facilitative effects of imagery encoding on memory performance (e.g., Foley et al, 2006Foley et al, , 2009 2 The participants in all four studies were native Polish speakers and were undergraduate students in one of the universities in Warsaw, Poland. 3 We provided the recall test after the whole set of lists because our main objective was to test general recall and recognition, not to verify the impact of recall on a later recognition test (Roediger & McDermott, 1995).…”
supporting
confidence: 77%
See 3 more Smart Citations